Membangun Jaringan Politik Kaum Milenial di Kecamatan Sayan untuk Meningkatkan Pengaruh Politik - Achyar, M. Sabran; Padilah, Ahirul Habib; Nurwijayanto, Nurwijayanto; Rudiyanto, Yustinus (Pencerah, 2023)
This research aims to record and analyze the process of building a political network among millennials in the Sayan District, focusing on enhancing political influence. The research objectives encompass understanding the purpose of establishing the millennial political network, the methodology employed in building the network, and the key findings of the study. The research methodology involves participatory analysis engaging millennials, local stakeholders, and political figures. This approach includes surveys, interviews, and observations to comprehend the dynamics of forming the political network and efforts to enhance political influence in the Sayan District. The research findings include the identification of the primary objectives of establishing the millennial political network, the strategies employed in the network-building process, and the positive impacts achieved in enhancing political influence at the local level. The outcomes of the research are expected to contribute to a better understanding of the role of millennials in the local political context and provide insights for stakeholders to improve millennial political participation in the future.